KOLA OGUNMOLA: A SOCIO-CULTURAL STUDY OF HIS FOLKLORIC PLAYS (1991)
The Yoruba modern travelling theatre traditions has been a major point of focus by some scholars of the performing arts in the recent past. Their interest in this tradition is probably due to its educative technique and its entertaining and didactic nature. Some of these scholars have deliberated on various aspects of Yoruba theatre and drama, and studied some of the Yoruba popular dramatists with the aim of highlighting their innovative techniques. In their studies, therefore, they have suggested several ways in which the Yoruba cultural heritage can be revived for the benefit of the resent generation and the future Nigerian gen rations. The renowned performing artists w o have been studied include the late Hubert Ogunde, the late Kola Ogunmola, Oyin Adejobi, the late Duro Ladipo, Moses Olaiya Adejumo (alias Baba Sala), and a host of others. Studies on these performing artists range from their organizational ability, their physical presence on stage, their innovative techniques, their style and their interest in traditional material for production, to language use and manipulation and their contributions to the socio-cultural, economic and moral development of the Yoruba society in particular and the Nigerian nation in general. Unfortunately, however, the present writer has discovered that not much has been done on the work of the late Kola Ogunmola who is generally believed to have been a seasoned and renowned performing artist in the 1950s and 1960s. Moreover, it has also been discovered that the folkloric plays of Ogunmola have been only briefly touched upon and analysed by scholars. In the light of this situation, the present writer decided to look more closely into the content of the late Kola Ogunmola's folkloric plays with the aim of analysing the philosophical thoughts behind them in a socio-cultural context. It is our hope that the findings of this research would be of benefit to the contemporary and future Yoruba societies and to the community of scholars world-wide. This is without prejudice to the enduring value of the plays themselves. The first chapter is an introductory one which discusses the rationale, conceptual framework and the scope of the study, the methodology followed and the life history and philosophy of the late Kola Ogunmola. A typological survey of Ogunmola's plays is made, while a thematic analysis of his folkloric plays is briefly attempted. Finally, the significance of folklore in Yoruba socio-cultural life is discussed at some length. The second chapter attempts a review of approaches to folklore, literature and theatre studies and highlights some topics which have been discussed by previous writers on the Yoruba travelling theatre tradition and on the personality of the late Kola Ogunmola. The views, comments and submissions of these writers are carefully examined in order to find out which, among these, still remain valuable or relevant and which ones need to be set aside. Chapter Three makes an in-depth study and attempts a critical discussion in a textual analysis of each of Ogunmola's folkloric plays and finally makes some comments on the socio-cultural and economic messages in the plays with particular reference to the Yoruba people of Southern Nigeria. In Chapter Four, the stylistic features of the Yoruba language and Ogunmu1a's expertise in the manipulation of the language and the musico-poetic aspects of Ogunmola's folkloric plays are discussed. Chapter Five concludes the dissertation with comments, views and submissions on Ogunmola's contribution to modern theatre and drama and his philosophical message, as revealed in the plays, to both the people of his time and to future generations. Finally, it touches upon the future of the modern Yoruba travelling theatre and the benefits that are expected to be derived from it.